THE EFFECT OF SOLVENT TYPE ON FLAVONOID LEVELS OF MORINGA LEAF EXTRACT (MORINGA OLEIFERA L.) (Journal of Health, Technology and Science (JHTS), 2024)
This study aims to determine the effect of the type of solvent on the levels of flavonoids in Moringa leaf extract (Moringa oleifera L.) and the differences in levels of flavonoids in each solvent. The method used in this study was a laboratory experimental method that included the extraction stage of Moringa leaves using three solvents, namely ethyl acetate, methanol, and 96% ethanol; the phytochemical screening test for the flavonoid compounds of Moringa leaf extract; and the flavonoid compounds test using UV-Vis Spectrophotometry. The results showed that there was an effect of the solvent type on the levels of flavonoid compounds in Moringa leaf extract (Moringa oleifera L.), and there were differences in the highest levels of flavonoids obtained in methanol extract of 2708.10 mg/L, 96% ethanol of 1890.24 mg/L, and ethyl acetate of 717.62 mg/L.